Psychopathy: what are fearless people afraid of? - Coelho, Carlos M.; Araújo, Ana S.; Suttiwan, Panrapee; Barbosa, Fernando; Bento, Tiago; Zsido, Andras N. (Frontiers in Psychiatry, 2025)
IntroductionHistorically, the distinction between primary and secondary psychopathy has focused on fear or lack thereof and limited anxiety symptoms. Individuals high in primary psychopathy traits often exhibit little or no anxiety or fear. These traits are key features, and several methods used to differentiate primary and secondary psychopathy emphasize fear and anxiety as key discriminators. However, there is limited evidence on what individuals high in psychopathy traits might specifically fear. Most previous studies have either included specific phobias within an anxiety cluster, thereby precluding the possibility of observing the number and type of phobias reported by participants with psychopathic traits, or have addressed specific phobias in general without further detailing the specific fears to which these participants were referring.MethodsThis study attempts to address this evidence gap by using the Levenson Self-Report Psychopathy Scale to measure psychopathy and the Fear Survey Schedule III to measure phobic anxiety.ResultsResults indicate that individuals with higher levels of secondary psychopathy report a greater number of specific fears. In contrast, those with primary psychopathy show fear or discomfort primarily related to seeing naked people. DiscussionThese findings are discussed in detail.